Religious transit and multiple religious belonging among sexual minorities in Brazil: a mixed-method study - Felix Ribeiro, Matheus Fernando; Gomes Dolenga , Fabrini; Soleiman Franco, Renato (Numen, 2025)
This study investigated the relationships between religious identity and gender/sexual orientation among sexual minorities in Brazil, focusing on religious transit and multiple religious belonging. A total of 151 participants answered questionnaires about their previous and current religious identities, the reasons for switching, and the impact of their sexuality. The results suggest significant differences in religious transit according to identity. Qualitative analysis revealed three central categories: rupture and redefinition of spirituality, ambivalence in religious spaces, and suffering and conflict with religious morality. Approximately one third of the sample reported multiple religious belonging, a proportion three times higher than the national average. There was a trend toward disaffiliation from religion altogether and from traditional Christian denominations, with increased affiliation to Afro-Brazilian, Buddhist, Indigenous, and esoteric religions. Religious transit emerged as a strategy for maintaining mental health, and religious identity was understood as a continuous rather than a dichotomous variable.